EVALUASI PENGGUNAAN ANTIBIOTIKA TERHADAP PASIEN PNEUMONIA KOMUNITI DI RUMAH SAKIT IBNU SINA MAKASSAR - Usman, Dwi Anggara Putri; Herman, Hendra; Emelda, Andi (Fakultas Farmasi UMI, 2014)
Pneumonia is an infectious disease that causes acute inflammation of the lung parenchyma. The purpose of this study was to compare the use of antibiotics and the appropriateness of antibiotics use in between Community acquired pneumonia patients include accuracy, appropriateness and administration duration of antibiotics compared with governance of community aquired pneumoniaÂ treatment Infectious Diseases Society Of America (IDSA) and World Health Organization (WHO). This study was retrospective descriptive survey with sampling technique that was purposive sampling. The results showed that the type of antibiotic used was ampicillin, ceftriaxone, ciprofloxacin, Cefepime, pentohydrate ceftazidime, cefotaxime, Cefadroxil, cefditoren pivoxil, azitromicin, meropenem, gentamicin and levofloxacin. The accuracy of antibiotics to community Ibnu Sina hospital based management of IDSA and the WHO as many as 31(62.0%) patients who appropriate and 18(36.0%) patients inappropriately. The accuracy of dose antibiotics in community acquired pneumonia patients Ibnu Sina hospital based management of IDSA and the WHO as many as 31 (62.0%) patients who appropriate and 18(36.0%) patients inappropriately. The duration of antibiotics in community acquired pneumonia patients Ibnu Sina hospital based management of IDSA and the WHO as many as 29 (58.0%) patients who appropriate and 20 (40.0%) patients inappropriately.